Strategia oraz taktyka zapobiegania i zwalczania czynów zabronionych związanych z bezpieczeństwem meczu piłki nożnej jako problem polityki kryminalnej - Chlebowicz, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper is devoted to the problem of countering football related crimes in the context of criminological theories, including the so-called policy analysis. The author highlights the strategy that was used during the Euro 2012. The attention is paid to the various techniques, eg. friendly but firm, use of CCTV cameras, surveillance. The article shows the response of the Polish Police and other agencies to groups of football hooligans.
Keywords: przestępstwa piłkarskie; przeciwdziałanie przestępczości; zapobieganie przemocy w sporcie; policja; Euro 2012 (piłka nożna)